Development and application of an indirect enzyme-linked immunosorbent assay using recombinant truncated Cap protein for the diagnosis of porcine circovirus-like virus P1 - Wen, Li-bin (BMC Vet Res, 2016)
BACKGROUND: Porcine circovirus-like virus P1 is a newly discovered virus. To date, there has been no specific serological assay for use in the diagnosis of P1 infection. RESULTS: Because P1 has high homology to porcine circovirus type 2 (PCV2) at the nucleotide level, the C-terminal portion of the capsid protein (amino acids 73–114), a discriminative antigen, was expressed in a prokaryotic expression system. The recombinant product (rctCap), composed of three identical repeated domains, was shown to be strongly immunoreactive to P1-specific serum. This assay was validated by comparison with an indirect immunofluorescence assay (IFA). The diagnostic sensitivity and specificity of the rctCap enzyme-linked immunosorbent assay (ELISA) developed in this study are 93.6 % and 98.3 %, respectively, compared with the results from IFAs on 450 sera samples from pigs. CONCLUSIONS: The indirect ELISA that we developed with rctCap, the recombinant capsid fragment containing the 217–342 nt repeat domain, was sensitive, specific, and suitable for the large-scale detection of P1 infections in swine.